2022
DOI: 10.1002/ece3.8829
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evolution of a more restrained clutch size when filial cannibalism is prevented in burying beetlesNicrophorus vespilloides

Abstract: The overproduction of offspring is commonly associated with high hatching failure and a mechanism for dispensing with surplus young. We used experimental evolution of burying beetle populations Nicrophorus vespilloides to determine causality in these correlations. We asked does eliminating the mechanism for killing “spare” offspring cause the evolution of a more restrained clutch size and consequently select for reduced hatching failure? N . vespilloide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…We found relatively little evidence of coadaptation between parents in clutch size, however. Clutch size in these experimental populations appeared to be only weakly influenced by the male’s population of origin and instead to be primarily determined by female size, carcass mass, and the female’s population of origin (Duarte et al 2021; Rebar et al 2022).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We found relatively little evidence of coadaptation between parents in clutch size, however. Clutch size in these experimental populations appeared to be only weakly influenced by the male’s population of origin and instead to be primarily determined by female size, carcass mass, and the female’s population of origin (Duarte et al 2021; Rebar et al 2022).…”
Section: Discussionmentioning
confidence: 91%
“…During the first thirteen generations of experimental evolution, the No Care lines rapidly adapted to a life without parental care (Schrader, Jarrett, and Kilner 2015a; Schrader et al 2017), through divergent phenotypic adaptations in both larval (Jarrett et al 2018a; Jarrett et al 2018b; Rebar et al 2020) and parental traits (Jarrett et al 2018a; Duarte et al 2021). In particular, No Care parents rapidly evolved to lay smaller clutches on small carrion (Rebar et al 2022), which could have resulted from males evolving to become less effective at stimulating female fecundity and/or females evolving to produce fewer eggs (Pascoal et al 2018). In addition, No Care parents evolved to become more efficient and more effective at converting carrion into a nest for their larvae, and in this way increased their offspring’s chance of surviving without post-hatching care (Duarte et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These two regimes of care were imposed in the same way on each population for over 50 generations in total. We have previously reported that the No Care populations rapidly evolved and adapted to the absence of post-hatching care [14][15][16][17][18][19][20][21] . After 13 generations, parents in the No Care populations had evolved to 'frontload' parental care and put more effort into nest-preparation than Full Care parents 15 .…”
Section: Introductionmentioning
confidence: 99%
“…During the first 20 generations of experimental evolution, the NC lines adapted rapidly to our experimental intervention [ 34 , 35 ] and exhibited divergent phenotypes in both larval [ 36 38 ] and parental traits [ 29 , 36 , 39 ]. Crucially, all the adaptations to a life without parental care that occurred within 20 generations of experimental evolution were consistent between replicate populations, including the timing of making the feeding incision [ 29 , 36 ].…”
Section: Introductionmentioning
confidence: 99%